The functional training bible - Bruscia, Guido, ....- (Maidenhead : Meyer & Meyer Sport, 2015)
Bodyweight and eveyday equipment workouts - increased mobility and stability - the natural form of strength training - Discover functional training like you ve never seen or experienced!. This training is easy, fast and fun and it will revolutionize your health and athletic performance. It will become a new way of life! Functional training is a scientific method for personal training, workouts at the gym, at home or outdoors. The book is divided into three parts: The first, theoretical part explains the why at the foundation of functional training; the second, practical part contains bodyweight exercises and exercises with various tools (sandbags, medicine ball, kettlebells). The final section proposes several specific training programs for strength, hypertrophy and weight loss. Welcome to the revolution in functional training. Get your focus and follow it!
More than 200 exercices and 600 pictures
Keywords: Krachttraining